Knowledge of molar incisor hypomineralization among physicians and dentists - Ghazal, Ebtehal; Moharir, Madhavi; El-Badrawy, Wafa; Yavuz, Yasemin; Kulkarni, Gajanan (Faculty of Dental Medicine Universitas Airlangga, 2023)
Background: Molar incisor hypomineralization (MIH) is a global dental condition. Early intake of antibiotics can increase the risk of MIH. Purpose: To assess the knowledge of physicians and dentists on MIH and its associations with antibiotics exposure during early childhood. Methods: This cross-sectional study surveyed the above health professionals utilizing an electronically distributed questionnaire. The chi-square test was used to compare differences in levels of knowledge between the study groups. Results: There were 335 participants in the study; general physicians (n=79), pediatricians (n=98) and dentists (n=158). A significantly lower proportion of general physicians and pediatricians had knowledge of MIH compared to dentists (19% and 18% vs. 82%, respectively, P<0.001). There was no statistically significant difference between all groups regarding their knowledge about the association between antibiotics prescribed during the first four years of life and MIH development (P=0.07). Conclusions: Physicians and pediatricians lacked knowledge about the dental condition of MIH. Most study respondents did not know the association between frequent antibiotic intake during early childhood and the development of MIH. Since medical practitioners are more likely to prescribe antibiotics and have a greater impact on early childhood health, raising awareness of MIH and its relationship with antibiotic exposure in early life among medical practitioners is essential.